PROGRAM PENDIDIKAN PENGEMBANGAN KEPEMIMPINAN SEBAGAI UPAYA PEMBERDAYAAN PADA PEMUDA - Arief, Aqil Wilda; Rahayu, Ety (Social Welfare Study Program, 2020)
Abstrak. This study attempts to see the implementation of leadership development education programs as an effort to empower youth as an effort to empower youth. The leadership development education program that was highlighted was a leadership development program implemented by the non-profit organization named Rumah Kepemimpinan. This study will discuss how the implementation of leadership development education programs is one of the steps to empower youth, especially in capacity building related to aspects of knowledge, skills and attitudes. This study is taken with a qualitative approach that will involve a number of informants from internal organizations and beneficiaries. From the results obtained, the beneficiaries felt significant results, especially in the aspect of capacity building in the aspects of knowledge, skills and attitudes that were more optimal, targeted and measured. Abstrak. Studi ini mencoba untuk melihat pelaksanaan program pendidikan pengembangan kepemimpinan sebagai upaya pemberdayaan pemuda sebagai salah satu upaya dalam pemberdayaan pemuda. Program pendidikan pengembangan kepemimpinan yang disoroti adalah program pengembangan kepemimpinan yang dilaksanakan oleh organisasi non-profit Rumah Kepemimpinan. Studi ini akan membahas bagaimana pelaksanaan program pendidikan pengembangan kepemimpinan menjadi salah satu langkah pemberdayaan pemuda terutama pada peningkatan kapasitas yang berhubungan dengan aspek pengetahuan, keterampilan dan juga sikap. Studi ini diambil dengan pendekatan kualitatif yang akan melibatkan sejumlah informan dari internal organisasi dan peserta program. Dari hasil yang didapat, peserta program merasakan hasil yang signifikan terutama dalam aspek peningkatan kapasitas pada aspek pengetahuan, keterampilan, dan sikap yang lebih optimal, terarah dan terukur.